OPTIMIZING SCAFFOLDING IN GENRE-BASED APPROACH TO IMPROVE STUDENTS' WRITING ANALYTICAL EXPOSITION IN AN EFL CLASSROOM CONTEXT - Lala Nurlatifah, - (2022)
Writing is often perceived as the most challenging skill for EFL learners. Indonesian EFL learners often encounter problems in writing, particularly in analytical exposition text, which negatively affects their exam results. The preliminary study of the present research showed that students faced problems with writing aspects of analytical exposition, psychological issues, and negative perceptions towards writing. As a result, this study focuses on overcoming the problems by implementing the scaffolding strategy in the teaching and learning process. Framed in classroom action research, this study aims to investigate how using scaffolding as a strategy in teaching writing (Walqui, 2006; Boldrini & Catteneo, 2014; Howell, 2018) can improve students' writing in analytical exposition text. This qualitative study employed document analysis, observation, and interviews to answer the research questions. The participants of this study were 26 EFL students in an Islamic high school in Bandung, and six students participated in interview sessions. The result indicated that the scaffolding process implemented in two cycles of action research improved students' skills in writing analytical exposition text in all aspects of writing: content, organization, grammar, vocabulary, and mechanics. Besides, students also showed a positive perception toward implementing scaffolding through various activities in the classroom. This study recommends the scaffolding writing be applied using multiple online tools in more diverse educational settings since the rapid progress of information technology enables learners to acquire knowledge and improve skills online. Moreover, learning is no longer restricted to paper-based formats nowadays.